Personal values and unsanctioned aggression inherent in contact sports: The role of self-regulatory mechanisms, aggressiveness, and demographic variables - Albouza, Y.; Wach, M.; Chazaud, P. (European Review of Applied Psychology, 2020)
Introduction: To date, research-examining factors related to the sociocognitive self-regulatory mechanisms governing unsanctioned aggression have received scant attention in applied sport psychology. Objective: A mediating model as influenced by various demographic variables was applied to explore the relationships between athletes` personal values and their unsanctioned aggression directly and indirectly through the mediating role of resistive self-regulatory efficacy, moral disengagement, and aggressiveness. Method: A sample of 301 French competitors of different age (young: n = 200 and adult: n = 101), gender (male: n = 172 and female: n = 129), type of sport (high: n = 131 and low contact: n = 170), level of competition (beginner: n = 115, intermediate: n = 110, and advanced: n = 76), and length of practice (brief: n = 109, intermediate: n = 49, and extensive: n = 143) completed a questionnaire assessing the aforementioned variables. Results: Structural equation modelling demonstrates that self-transcendence and self-enhancement values have only indirect negative and positive effects, respectively, on unsanctioned aggression through the full mediating effect of the mediators. Also, age, gender, and type of sport were predictive only of some personal values and mediators. Conclusion: These findings offer evidence that resistive self-regulatory efficacy, moral disengagement, and aggressiveness are mediators that fully govern the impact of athletes` personal values and certain demographic variables on their unsanctioned aggression. Several limitations, implications and suggestions for further research are discussed.